(untitled) (World Science, 2019)
Article analyses the thematic, lexical and grammatical and functional- stylistic appearance of slang in the language of mass media on the structural and semantic level; ways of entry of sang of certain thematic groups into the system of modern Ukrainian language are traced; expressive-emotional potential of stylistic reduced vocabulary in modern publicist discourse is analyzed; the semantic modifications and functional specificity of slang were clarified. The attempt to analyze the peculiarities of appearance, development and functioning of slang in modern periodicals was made. It was noticed, that mass media language and spoken language today are the only sources for scientific generalization of slang. During the studying of slang, the question about what categories and language means were activated, motioned, mobilized for playing functions of language as the most important mean of persons’ communication was researched.